Validity of Visible Ectoparasite Intensity As a Non-invasive Biomarker for Fish welfare: Parasitic Copepod, Lernantropus kroyeri in Sea Bass As an Example - Hijran Yavuzcan (Aquatic Sciences and Engineering)
Ensuring fish welfare is essential from the ethical, legal, environmental, economic, and social perspectives. It plays a vital role in maintaining the health and sustainability of aquaculture practices while respecting the intrinsic value and welfare of the fish themselves. The presence of reliable welfare assessment schemes is of utmost importance to appraise the well-being of animals in aquaculture and uphold stringent welfare standards. In determining fish welfare, conducting welfare assessments with non-invasive biomarkers is crucial thus the primary objective of this study is to explore the potential usability of visible parasites as welfare biomarkers in fish without causing any harm to the fish. In this research, certain secondary stress indicators (hematocrit, plasma glucose and lactate) were employed as biomarkers for assessing the well-being of European sea bass (Dicentrarchus labrax). The study aimed to investigate whether there is a possible correlation between the presence of visible ectoparasites on the gills (specifically, the Copepod parasite, Lernantropus kroyeri) and the aforementioned stress parameters. Thus, in this study, the examination was conducted to establish the validity of ectoparasites as non-invasive biomarkers for evaluating the welfare of fish. The results showed that there was a statistically significant relationship between the intensity of ectoparasites and the stress parameters used as indicators of welfare. The observable presence and intensity of ectoparasites on the gills of the fish can be proposed as a non-invasive biomarker for evaluating fish welfare in aquaculture.